1963
DOI: 10.1021/bi00906a029
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Avian Ovomucoids*

Abstract: Comparative physical and chemical studies were performed on three avian qvomucoids: chicken ovomucoid (a trypsin inhibitor), turkey ovomucoid (a trypsin and chymotryps ininhibitor), and pheasant ovomucoid (a chymotrypsin inhibitor). The amino acid composition and the carbohydrate contents have been determined. All three ovomucoids are stable to heating a t 80 ' at pH < 9, but heating to 100 O at p H 6 or to 80 O a t pH 9 results in a rapid loss of inhibitory activity for all three ovomucoids. They are also res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1965
1965
1991
1991

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Tyrosyl acetylation was determined from the decrease in molar absorptivity using a factor of 1160 per tyrosyl residue per mole, as described in the text. 9 Hermans (1962).c Crammer and Neuberger (1943).d Havsteen and Hess (1962).6 Stevens and Feeney (1963). zShugar (1952); Tanford et ai (1955a).0 Inada etal.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosyl acetylation was determined from the decrease in molar absorptivity using a factor of 1160 per tyrosyl residue per mole, as described in the text. 9 Hermans (1962).c Crammer and Neuberger (1943).d Havsteen and Hess (1962).6 Stevens and Feeney (1963). zShugar (1952); Tanford et ai (1955a).0 Inada etal.…”
Section: Resultsmentioning
confidence: 99%
“…Lineweaver and Murry (1947) demonstrated that the ovomucoid heated at 80°C for 30 min in an acidic or neutral solution retained more than 90% of the activity. Stevens and Feeney (1963) found that 30% of the activity still remained after heating the protein at 100°C for 15 min at pH 6. Fraenkel-Conrat et al (1952) showed that 80% and 62% of the activity remained when the ovomucoid was heated at 90°C for 15 min at pH 5 and pH 7, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…ovomucoid and 1.6 for chicken ovoinhibitor. Molar ratios of inhibitor to enzyme calculated by assuming the molecular weight of 28000 for turkey ovomucoid [27], 46500 for chicken ovoinhibitor [17] and 25800 [l] for porcine elastase are 0.92 and 0.89 respectively which indicate 1 : 1 molar complex. The formation of complexes between elastase and both inhibitors was further demonstrated by means of electrophoresis.…”
mentioning
confidence: 99%